Preparation of Ni/ZSM-5 and Mo/ZSM-5 catalysts for hydrotreating palm oil into biojet fuel - Trisunaryanti, Wega; Wijaya, Karna; Tazkia, Aulia Meylida (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2024)
With the increasing demand for fuel for global usage and CO2 emissions, greener alternatives are needed, especially in biojet fuel production. Catalyst preparation involves the impregnation of Ni and Mo metals into H-ZSM-5 using a dry impregnation method with spray deposition, resulting in Ni/ZSM-5 and Mo/ZSM-5 catalysts. Catalyst characterization utilizes FT-IR, XRD, SAA, SEM-EDX, XRF, and NH3-TPD instruments. The activity and selectivity tests of the catalysts were conducted in the hydrotreating of palm oil using Ni/ZSM-5 monolayer, Ni/ZSM-5 bilayer, Mo/ZSM-5 monolayer, Mo/ZSM-5 bilayer, as well as Ni/ZSM-5 bottom-layer and Mo/ZSM-5 top-layer arrangements. The result showed double-layer Ni/ZSM-5 as the best catalyst in activity and selectivity in producing biojet fuel fractions with consecutive conversion, selectivity, and yield of 29.71%, 84.76%, and 24.34%, respectively. The layers of catalyst affected the catalytic activity and selectivity, resulting in a higher yield.